Manajemen Pemberian Foot Massage sebagai Intervensi Keperawatan Maternitas Nyeri Akut Akibat Post Operasi Sectio Caesarea di RSD Gunung Jati Kota Cirebon - Marwati Marwati; Tasya Dwi Amanda (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2025)
Caesarean section (CS) is a surgical delivery method whose incidence continues to increase globally. The World Health Organization (2021) reports that approximately 21% of births worldwide are by CS, and this figure is expected to increase to 29% by 2030. In Indonesia, 21.4% of mothers still experience labor complications, while in Cirebon City, approximately 2,700 mothers gave birth in 2024. One of the main problems after CS is acute pain, which is reported to be experienced by 60% of patients within the first 24 hours despite analgesic therapy. This condition can affect patient comfort, sleep quality, and mobility. Therefore, additional safe and effective interventions are needed to help reduce postoperative pain. One non-pharmacological method that has proven beneficial is foot massage, which can increase relaxation, improve blood circulation, and reduce pain perception. This case study was conducted on Mrs. L, a post-CS patient at Gunung Jati Regional Hospital. Foot massage intervention was given for 15 minutes, twice daily, for three consecutive days. Pain levels were measured using the Numerical Rating Scale (NRS). The results showed a decrease in pain from a scale of 7 before the intervention to a scale of 4 after three days of foot massage. The patient reported feeling more comfortable, improved sleep quality, and improved mobility, with no side effects observed. The conclusion of this case study is that foot massage therapy is effective in reducing acute pain in post-C-section patients and can be used as an additional intervention in maternity nursing practice. Nurses are advised to implement this therapy as part of comprehensive care to help reduce pain from surgical wounds and improve the quality of maternal recovery after C-section.